B1 artifact reduction in abdominal DCE‐MRI using kT‐points: First clinical assessment of dynamic RF shimming at 3T. Issue 6 (21st November 2017) - Tomi‐Tricot, Raphaël; Gras, Vincent; Mauconduit, Franck; Legou, François; Boulant, Nicolas; Gebhardt, Matthias; Ritter, Dieter; Kiefer, Berthold; Zerbib, Pierre; Rahmouni, Alain; Vignaud, Alexandre; Luciani, Alain; et al.
Abstract : Background: The excitation inhomogeneity artifact occurring at 3T in the abdomen can lead to dramatic loss of signal and contrast, thereby hampering diagnosis. Purpose: To assess excitation homogeneity and image quality achieved by nonselective prototypical kT ‐points pulses, compared to tailored static RF shimming, in clinical routine on a commercial dual‐transmit scanner. Study Type: Retrospective study with Institutional Review Board approval; informed consent was waived. Population: Fifty consecutive patients referred for liver MRI at a single hospital. Field Strength/Sequence: 3D breath‐hold dynamic contrast‐enhanced (DCE) MRI at 3T. Assessment: Flip angle homogeneity was estimated via numerical simulation based on measured static and RF field maps. In all, 20 of the 50 patients underwent DCE‐MRI while a pulse designer was present. The effect of RF shimming and kT ‐point pulses could be compared by repeating the acquisition with each transmit scheme before injection and in the late phase. Signal homogeneity, T1 contrast, enhancement quality, structure details, and global image quality were assessed on a 4‐level scale (0 to 3) by two radiologists. Statistical tests: Means were compared using Wilcoxon signed‐rank tests. Results: Normalized root mean square flip angle error was significantly reduced with kT ‐points compared to static RF shimming (8.5% ± 1.5% [mean ± standard deviation, SD] vs. 20.4% ± 9.8%; P < 0.0001). The worst case (heavy ascites) led to 13.0% (kT ‐points) vs. 54.9% (RF shimming). Global image quality was significantly higher for kT ‐points (2.3 ± 0.5 vs. 1.9 ± 0.6; P = 0.008). One subject's examination was judged unusable with RF shimming by one reader, none with kT ‐points. 85% of kT ‐points acquisitions were graded at least 2/3, and only 55% for static RF shimming. Data Conclusion: KT ‐points reduce excitation inhomogeneity quantitatively and qualitatively, especially in patients with ascites and prone to B1 shading. Level of Evidence: 1 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2018;47:1562–1571.